1989
DOI: 10.1080/10862968909547673
|View full text |Cite
|
Sign up to set email alerts
|

Developing Print Awareness: The Effect of Three Instructional Approaches on Kindergarteners' Print Awareness, Reading Readiness, and Word Reading

Abstract: This study investigated the effectiveness of three instructional approaches for developing kindergarteners' print concepts and print awareness. The study also sought to determine if developing children's print concepts exerted an influence upon their reading readiness and word reading ability at the end of kindergarten. Three intact kindergarten classrooms participated in the study with a total of 132 kindergarten students. The three instructional treatments consisted of (a) a "traditional readiness" approach-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

1990
1990
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 15 publications
0
7
1
Order By: Relevance
“…The proper comparison is 52% versus 14%, not 17 versus 9. These suggest that WL/LEA programs were effective in kindergarten, results further buttressed by adding the recently published Reutzel, Oda, and Moore (1989) study. The numbers also support the lack of overall difference between WL/LEA and BR programs in first grade, which is confirmed by the near zero mean effect size found from the meta-analysis.…”
Section: Marginal Totals and Other Technical Matterscontrasting
confidence: 54%
“…The proper comparison is 52% versus 14%, not 17 versus 9. These suggest that WL/LEA programs were effective in kindergarten, results further buttressed by adding the recently published Reutzel, Oda, and Moore (1989) study. The numbers also support the lack of overall difference between WL/LEA and BR programs in first grade, which is confirmed by the near zero mean effect size found from the meta-analysis.…”
Section: Marginal Totals and Other Technical Matterscontrasting
confidence: 54%
“…Reutzel, Oda, and Moore (), in an experimental study, found that an immersion approach to teaching CAP in kindergarten produced significant effects on reading readiness and word‐reading test scores. The immersion approach embedded CAP instruction in a shared reading where the teacher would operate on the enlarged print as if all children in the class were seated in her lap.…”
Section: Concepts About Print: Don't Assume It!mentioning
confidence: 99%
“…Some studies have demonstrated the positive effects of whole-language/ literature-based programs, in comparison with other programs, on print awareness and word reading acquisition among kindergarten children (Kasten & Clarke, 1989;Reutzel, Oda, & Moore, 1989;Ribowsky, 1985), while other studies have not revealed significant differences on standardized tests of decoding skills and reading readiness (Morrow, O'Connor, & Smith, 1990;Stahl & Miller, 1989). Based on their review of studies comparing conventional reading instruction (basal instruction) and the whole-language/language-experience approach, Stahl and Miller (1989) found that the latter was more effective in kindergarten than in first grade.…”
Section: Early Literacy Instruction and Learning In Kindergartenmentioning
confidence: 99%